The diameter increment of selected tree species in a secondary tropical forest in Sarawak, Malaysia - KARYATI KARYATI; ISA B. IPOR; ISMAIL JUSOH; MOHD. EFFENDI WASLI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Karyati, Ipor IB, Jusoh I, Wasli ME. 2017. The diameter increment of selected tree species in a secondary tropical forest in Sarawak, Malaysia. Biodiversitas 18: 304-311. The diameter at breast height (DBH) increments of dominant tree species in a secondary forest can determine forest growth in the area. This study was conducted to investigate the DBH increments of the nine dominant tree species in a secondary tropical forest. A total number of 180 trees representing nine species, seven genera, and six families were selected for the assessment of DBH increments during two years of study. Those nine species, namely: Acacia mangium Willd. (2.33 cm year-1), Endospermum diadenum (Miq.) Airy Shaw (1.05 cm year-1), Cratoxylum arborescens Blume. (0.96 cm year-1), Vernonia arborea Buch. Ham. (0.96 cm year-1), and Cratoxylum glaucum Korth. (0.80 cm year-1) had shown a high growth rate during the assessment, while the other four species such as Macaranga gigantea Mull. Arg., Macaranga triloba Mull. Arg., Euodia glabra (Bl.) Bl., and Vitex pubescens Vahl. had 0.53, 0.48, 0.37, and 0.30 cm year-1 in DBH increments, respectively. The average DBH increments for the entire selected species was 0.86 cm year-1 for periodic measurement and 0.75 cm year-1 for monthly measurement. This information is needed in order to understand the succession process in the secondary forests. It is important for the selection of the suitable species in a reforestation and a rehabilitation projects. Keywords: Diameter increment, fast growing species, secondary forest, selected speciesÂ